A bi-criteria combined evaluation approach for reinforcement effect of gravity dam with cracks. (15th August 2018) - Su, Huaizhi; Li, Jinyou; Wen, Zhiping; Zhou, Fengfeng
Abstract: The reinforcement measures, such as pre-stressed anchor cable and concrete anti-seepage layer covering original dam body, are often used to improve the structural stability, control the crack development and advance the carrying capacity of concrete dam engineering. This paper focuses on the reinforcement effect evaluation problem of gravity dam with cracks. Some mechanical and mathematical methods, such as the J integral and interaction integral methods in fracture mechanics, the support vector machine (SVM) method, are combined. According to the integrated criteria on crack behavior improvement and carrying capacity advancement, the implementation approach for reinforcement effect identification and long-term forecast of gravity dam with cracks is investigated. Firstly, considering the effect of reinforcement practice on structural behavior, stress field and strain field of original crack tip zone in gravity dam, the stress intensity factor (SIF) is taken to represent the combined action response of reinforcement practice and loads. To improve the computation efficiency and accuracy, which are the shortcomings existing in the conventional methods applied to the calculation of stress field with complex crack surface and crack tip, the improved J integral method is combined with the interaction integral method to calculate the SIF of crack tip in gravity dam after the reinforcement implementation. Then, the cracking safety of gravity dam is regarded as a goal, the SIF is regarded as a control index. A SVM method is proposed to determine the critical loads ensuring the cracking safety of gravity dam. An approach using two criteria on SIF and critical load is developed to implement the reinforcement effect evaluation of gravity dam with cracks. Lastly, an actual gravity dam undergoing reinforcement practice is taken as an example. The approach proposed in this paper is used to calculate the SIF of crack tip and the critical loads of cracking safety. The reinforcement effect identification and long-term forecast of gravity dam are fulfilled by analyzing the development of SIF and critical load.